Effect of Complexation on Antibacterial Activity of Some Cyanoacetyl Hydrazones Metal Complexes - Singh Sisodia, Gyan; Raipuriya, R.B.; Maurya, K.K.; Sitholay, O.V. (Asian Journal of Chemistry, 2010)
Some divalent metal complexes of cyanoacetyl acetic acid hydrazide (CAAH) cyanoacetyl benzalidene hydrazone (CABH) and cyanoacetyl 4-hydroxy 3-methoxy benzalidene hydrazones have been synthesized and effect of complexation on antibacterial activity have been studied. The modification in antibacterial behaviour of the ligands on complexation has revealed that some metal complexes are more potent than their corresponding ligand molecules and complexation enhances the antibacterial nature of cyanoacetyl hydrazones.